Multifocal pigmented villonodular synovitis in a child: A case report. Issue 33 (August 2016) - Zhao, Liang; Zhou, Kaiyu; Hua, Yimin; Li, Yifei; Mu, Dezhi
Abstract: Introduction: Pigmented villonodular synovitis (PVNS) is a rare, benign proliferative disorder of the synovial membrane that typically presents in adults and affects a single joint. Multifocal PVNS is very rare, particularly in childhood. We reported a rare case of multifocal PVNS affecting over 20 joints in a child. Clinical procedure: A 7-year-old female patient had a 6-month history of multifocal joints swelling with mild pain. She was diagnosed as polyarticular juvenile idiopathic arthritis at a local hospital. Naproxen, methotrexate, infliximab, and pavlin were used to treat the patient for 2 months. However, the treatment had no effect, the joints swelling remained. The patient was then transferred to our hospital. Physical examination revealed multiple joints swelling, especially in the shoulders joints. Puncture fluid from a shoulder joint was bloody. Magnetic resonance imaging (MRI) revealed synovial thickening and hemosiderin deposition. Biopsy of joint synovium found villous nodules, the invasion of foam cells, and hemosiderin deposition. By collecting all of the evidence, the diagnosis of PVNS was confirmed. Conclusions: PVNS was easily misdiagnosed as rheumatoid arthritis and the formal treatment was usually delayed. This case described here is the first case of PVNS involving such a large numbers of joints that has been reported in the literature.